Profil Kerapuhan dan Masalah terkait Obat pada Kelompok Lanjut Usia di Panti Jompo Kota Surabaya - Verlita Evelyn Susanto; Adji Prayitno Setiadi; Bobby Presley; Steven Victoria Halim; Eko Setiawan (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Frailty and drug related problems (DRPs) are common among elderly who lives in the nursing home. There is currently limited information available regarding the profile of frailty and DRPs among elderly living in the nursing homes in Indonesia. This project aims to describe the profile of frailty and DRPs among nursing home residents in Surabaya. This cross-sectional study was conducted in three nursing homes in Surabaya. Integrated Systematic Care for older People (ISCOPE) questionnaire was used to identify the frailty profile among participants. Beers Criteria, screening tool of older person’s prescriptions (STOPP), geriatric dosage handbook and drug interactions analysis and management were used as tools to identify and analyse drug related problems in this study. Several DRPs were identified in this study including inappropriate drug choices, drugs interaction, and inappropriate dose of drugs. In total, 68 elderly were recruited in this study and 41.18% of them were classified as frail older people. There was no drugs interaction with “clinical significance” being identified, however, inappropriate dose of drugs and potentially inappropriate drug choices were found in 58.82% and 19.12% of nursing home residents, respectively. Findings regarding the profile of frailty and DRPs among elderly may indicate the needs to implement an appropriate intervention strategic in order to optimize the use of medications among nursing homes-dwelling elderly people.